2000
DOI: 10.1074/jbc.m002047200
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of a Calmodulin-dependent Calcium Pump Involves a Structure in the Stalk That Connects the Transmembrane Domain to the ATPase Catalytic Domain

Abstract: The regulation of Ca 2؉ -pumps is important for controlling [Ca 2؉ ] in the cytosol and organelles of all eukaryotes. Here, we report a genetic strategy to identify residues that function in autoinhibition of a novel calmodulin-activated Ca 2؉ -pump with an N-terminal regulatory domain (isoform ACA2 from Arabidopsis). Mutant pumps with constitutive activity were identified by complementation of a yeast (K616) deficient in two Ca 2؉ -pumps. Fifteen mutations were found that disrupted a segment of the N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…There are a few known mutations of P-type ATPases that increase activity but these mutations relieve negative regulation to restore constitutive activity (34)(35)(36). The best-characterized example is for plasma membrane calcium ATPase (PMCA), which has an autoinhibitory domain that binds calmodulin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few known mutations of P-type ATPases that increase activity but these mutations relieve negative regulation to restore constitutive activity (34)(35)(36). The best-characterized example is for plasma membrane calcium ATPase (PMCA), which has an autoinhibitory domain that binds calmodulin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Pmr1, a Golgi Ca 2ϩ /Mn 2ϩ -ATPase, has an EF-hand motif in the N-terminal part of the A-domain, presumably working as a Ca 2ϩ -dependent regulator of the ATPase (49). A plant Ca 2ϩ -ATPase (ACA2 from Arabidopsis) has an N-terminal regulatory domain, which interacts with the stalk region (50). Some heavy metal pumps have additional metal ion binding domains at the C terminus (5).…”
Section: Discussionmentioning
confidence: 99%
“…1D), likely because the N-terminal part of BON1 targets to the PM and inhibits the fusion protein from going to the nucleus to activate gene expression. Because the segment I of ACA10 contains the putative autoinhibitory motif that confers autoinhibition of many ACA proteins (Bonza et al, 2000;Curran et al, 2000;Geisler et al, 2000), BON1 may regulate ACA10 activity by binding to this motif or its nearby sequences. We found that ACA10, like BON1, is a negative regulator of plant immunity.…”
Section: Bon1 and The Calcium Atpase Aca10 Interact Physicallymentioning
confidence: 99%